Experiences of health professional students’ participation in the GEMx regional elective exchange program in Africa - Nawagi, Faith; Iacone, Anna; Seeling, Justin; Yuan, Shiyao; Mukherjee, Snigdha (Frontiers in Education, 2023)
Background Given the significant gap in International Electives (IEs) opportunities for African health professions students, ECFMG|FAIMER through its Global Educational Exchange in Medicine and other health professions (GEMx) program launched a pilot African regional elective exchange program in 2016. During IEs, students have a choice of discipline they would like to learn, and the location, often at a host institution in a different country. This study provides an overview of health professional students’ experiences through participation in the pilot GEMx regional elective exchange program in Africa. Methods This was a quasi-experimental, single-group post-test-only study using the survey method. Data were collected online using a self-administered survey through SurveyMonkey. Students (N=107) received emails with a link to the survey as they completed the electives. The survey was open for a month for each student and weekly reminders were sent. Results The survey obtained a 100% response rate. All postgraduate and undergraduate students from various professional training programs (n =107) reported gaining knowledge that was applicable back home. Over 43.4% (n=46) reported having formed professional networks that are valuable for career progression. More than half 59.8% (n=64) gained clinical skills and learned various procedures while 26.2% (n=28) recognized the need for increased reliance on history taking for disease diagnosis. More than a third, 34.6% (n=37) appreciated the different cultures and the effect of cultural beliefs on health outcomes. Discussion and Conclusions The GEMx regional elective exchange program in Africa provided a useful platform that enabled health professional students at undergraduate and postgraduate levels in their respective disciplines to gain enhanced perspectives on health issues, acquire clinical knowledge and skills applicable to their home country, strengthen personal and professional development, and develop positive attitude change in various health care delivery approaches.